PENGARUH KUALITAS PELAYANAN, HARGA, DAN KERAGAMAN PRODUK TERHADAP KEPUASAN PELANGGAN CAFE STOVE SYNDICATE SEMARANG - Vivian Avianty; Handoyo Djoko Waloejo (Universitas Diponegoro, 2019)
Nowadays, cafe has become one of the most promising business run by businessman and could attract people’s interest alongside with the modern lifestyle, especially for adolescents and adults to enjoy their products or even just hanging out with friends. Generally, cafe gives nice atmosphere on its room, unique concept, and modern which basically different compare by restaurants. Social media also has big contribution through market their products and cafe’s room pictures or gain endorsement to interest people easily. One of cafe in Semarang that still exist until now is Cafe Stove Syndicate. This research has its aim to determine and measure the effect of service quality, price, and product diversity to customer satisfaction. This research is an explanatory research and the technique of collecting data used is non probability sampling with the approach of purposive sampling and incidental sampling, and collecting data by using questionnaire as its instrument. The amount of samples that had taken is 100 respondents. This research apply quantitative analysis, with validity test, reliability test, correlation coefficient, determination coefficient, simple and multiple regression test, significance of t test, and significance of F test using SPSS for Windows 21 Version The result of this research shows that service quality, price, and product diversity have significant and positive impact to customer satisfaction. According to the analysis, service quality has the amount of 18,4% impact contribution. Price has the amount of 22,8% impact contribution, and product diversity has the amount of 19,4%. Simultaneously, service quality, price, and product diversity have the amount of 35,1% impact contribution to customer satisfaction.